The effects of birth spacing on early childhood development in high-income nations: A systematic review - Dhamrait, Gursimran; Fletcher, Tess; Foo, Damien; Taylor, Catherine L.; Pereira, Gavin (Frontiers in Pediatrics, 2022)
Abstract Objective: To systematically review the literature on the associations between birth spacing and developmental outcomes in early childhood (3 to 10 years of age). Studies examining the associations between interpregnancy intervals and child development outcomes during and beyond the perinatal period have not been systematically reviewed. Methods: We searched Ovid/MEDLINE, Global Health, PsycINFO, EMBASE, CINAHL Plus, Educational Source, Research Starters, ERIC, Scopus, PubMed, Social Science Research Network database, and ProQuest's Social Sciences Databases for relevant articles published between 1 January 1989 and 25 June 2021. Studies published in English, conducted in populations residing in high-income countries with any measure of birth spacing and child development outcomes among children aged <10 years were included. Two authors independently assessed the eligibility of studies and extracted data on the study design, setting and population, birth spacing, outcomes, and results. Results: The search yielded 1,556 records, of which seven studies met the inclusion criteria. Five of these seven studies used birth intervals as the exposure measure. Definitions of exposure differed between the studies. Three studies reported an association between short birth spacing and poorer child development outcomes and two studies reported an association between long birth spacing and poorer child development outcomes. Conclusions: Currently, limited evidence suggests that the adverse effects of sub-optimal birth spacing are observable beyond infancy.